Anti-IL-12 and anti-TNF antibodies synergistically suppress the progression of murine collagen-induced arthritis. - Butler, D; Malfait, A; Maini, R; Brennan, F; Feldmann, M (1999)
The co-ordinate role of the Th1 cytokine IL-12 and the proinflammatory cytokine TNF in arthritis was explored using the DBA/1 mouse model, collagen-induced arthritis (CIA). In this study, mice with established arthritis were treated with anti-IL-12 and/or anti-TNF antibodies for 10 days from the onset of disease. Clinical assessment showed that the combined antibody treatment ameliorated disease severity to a greater extent than anti-TNF alone. Supporting these observations, histological analysis revealed that there was a reduced joint damage in the mice that received combined anti-IL-12 and anti-TNF treatment, compared to the other treatment groups. Anti-IL-12 had no statistically significant effect on the clinical outcome of disease. The combination of anti-IL-12 and anti-TNF treatment was found to reduce collagen type II (CII)-specific lymph node cell IFN-gamma production and proliferation, as well as decrease the anti-CII IgG2a:IgG1 ratio more effectively than either treatment alone. When the antibodies were added to synovial cells from arthritic mice and bone marrow macrophages in vitro, anti-TNF diminished IL-12 production, but anti-IL-12 had no effect on TNF production. These data suggest that, through the partial regulation of IL-12, TNF modulates the immune response in arthritis, as well as the inflammatory response. The synergistic action of anti-TNF and anti-IL-12 on CIA may provide a new therapeutic approach for treating rheumatoid arthritis.